2015
DOI: 10.17556/jef.53497
|View full text |Cite
|
Sign up to set email alerts
|

Tam Sayılar Konusunun Öğrenilmesi ve Öğretilmesinde Yaşanan Zorluklar ve Çözüm Önerileri

Abstract: ÖzetBu çalışmanın amacı, tamsayılar konusunun öğretiminde yaşanan zorluklara ilişkin ortaokul matematik öğretmenlerinin görüşlerini incelemek ve çözüm önerileri sunmaktır. Çalışma, Adıyaman il merkezindeki farklı okullarda görev yapan 38 ortaokul matematik öğretmeninin katılımıyla yürütülmüştür. Veri toplama aracı olarak, araştırmanın amacına uygun olarak hazırlanan iki açık uçlu sorudan oluşan bir form kullanılmıştır. Verilerin analizinde içerik analizi tekniği kullanılmıştır. Yapılan analizler sonucunda; öğr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
1
7
0
2
Order By: Relevance
“…On the other hand, as a result of the study, it was revealed that the students had the misconception of "some real-life situations are only represented by negative or positive integers", which is a type of overspecification. Similarly, Erdem et al, (2015) also revealed that students have difficulties in associating whole numbers with daily life.…”
Section: Results Discussion and Conclusionmentioning
confidence: 93%
See 3 more Smart Citations
“…On the other hand, as a result of the study, it was revealed that the students had the misconception of "some real-life situations are only represented by negative or positive integers", which is a type of overspecification. Similarly, Erdem et al, (2015) also revealed that students have difficulties in associating whole numbers with daily life.…”
Section: Results Discussion and Conclusionmentioning
confidence: 93%
“…that students have misconceptions such as writing the set of integers, understanding negative integers, determining the absolute value of an integer, and limited perception in making sense. Similarly, writing the set of integers (İşgüden, 2008), making sense of negative numbers (Altıparmak & Özdoğan, 2010;Erdem, Başıbüyük, Gökkurt, Şahin & Soylu, 2015), and determining and making sense of the absolute value of an integer (Şandır, Ubuz & Argün, 2007) revealed that students experienced some problems. It has been determined that students' mistakes in comparing and ordering negative and positive integers have an overgeneralization type of misconception.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Öğrencilerin negatif ve pozitif tam sayılara yönelik tahmin stratejilerinde negatif tam sayı tahminleri pozitif tam sayı tahminlerine göre daha az başarılıdır (Yoong ve Booth, 2015). Öğrenciler eksi (−) işaretini anlamlandırmada, eksi işaretinin günlük hayattaki karşılığını kavramsallaştırmada, negatif tam sayılarla çıkarma işlemi yapmada ve tam sayıları sıralamada sıkıntılar yaşamaktadır (Erdem, Başıbüyük, Gökkurt, Şahin ve Soylu, 2015;Yenilmez ve Bağdat, 2014).…”
Section: Introductionunclassified